UPAYA MENINGKATKAN KREATIVITAS MELUKIS TAS KAIN PADA REMAJA DESA SUKAMUKTI KECAMATAN BOJONGMANGU - Safitri, Anisa; Sundari, Kori; Rikmasari, Rima (Universitas Islam 45 Bekasi, 2024)
This paper aims to train teenagers in painting activities to increase their creativity. Because creativity is really needed now, because times are increasingly advanced. Children and teenagers must be as creative as possible in making things. With the existence of cellphones and other gadgets, painting activities are starting to be forgotten in this village, which has resulted in very few teenagers still painting, even though painting is an art that must always be maintained. Every human being has different creativity, it's just that we need to maintain this potential. By carrying out this activity, it is hoped that teenagers in Sukamukti Village can develop and maintain their creativity. In this service, community education methods are used by providing guidance before carrying out practical activities. The teenagers were asked to paint freely according to the ideas they had or received from each person. And those who took part in this activity were teenagers from Sukamukti Village, members of youth organizations, and Community Service students at the Islamic University 45 Bekasi. This activity was carried out in the Sukamukti Village area (TPQ Darrut Tawwabin Annahdliyyah), for one day. The conclusion of holding this activity is to increase and maintain the creativity of Sukamukti Village teenagers.